Chemical doping of MoS2 multilayer by p-toluene sulfonic acid. Issue 3 (4th June 2015) - Andleeb, Shaista; Kumar Singh, Arun; Eom, Jonghwa
Abstract: We report the tailoring of the electrical properties of mechanically exfoliated multilayer (ML) molybdenum disulfide (MoS2 ) by chemical doping. Electrical charge transport and Raman spectroscopy measurements revealed that the p-toluene sulfonic acid (PTSA) imposes n-doping in ML MoS2 . The shift of threshold voltage for ML MoS2 transistor was analyzed as a function of reaction time. The threshold voltage shifted toward more negative gate voltages with increasing reaction time, which indicates an n-type doping effect. The shift of the Raman peak positions was also analyzed as a function of reaction time. PTSA treatment improved the field-effect mobility by a factor of 4 without degrading the electrical characteristics of MoS2 devices.